Perbandingan antara Bone Patellar Tendon Bone Autograft dengan Hamstring Tendon Autograft pada Rekonstruksi Anterior Cruciate Ligament : Sistematik Review - Fuad Iqbal Elka Putra; Hanifah Hanum (Medula, 2023)
Anterior Cruciate Ligament is a ligament injury is the most common injury around knee and divided into partial tear or complete tear. The aim of this study is to compare the outcome between Bone Patellar Tendon Bone (BPTB) autograft versus Hamstring Tendon (HT) for ACL reconstruction. The outcomes were assessed with International Knee Documentation Committee (IKDC), Lysholm score, Tegner activity scale and donor site morbidity. This systematic review uses Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The articles were searched for studies that compared functional outcomes of ACL reconstruction between BPTB autograft versus hamstring tendon autografts with a minimum 6 months follow-up. We analayzed 8 studies that compare outcomes of BPTB autograft (862 patient) vs HT autograft (4.991 patient). There was no significant differences in a patient underwent ACL reconstruction with BPTB autograft vs HT autograft the outcomes by IKDC score, Lysholm score and Tegner activity scale. In one study showed was significant in donor site morbidity where BPTB autograft makes postoperative pain during kneeling higher than HT autograft in 10 years follow up (BPTB 64%, HT 33%, p value 0.019) and the prevalence in pain during squatting BPTB was higher than HT autograft in 10 years follow up (BPTB 55%, HT 29%, p value 0.046). This study concluded there was no significant difference of comparison between BPTB autograft and HT autograft group after ACL reconstruction. Donor site morbidity most commonly occured in BPTB group than HT gorup. Keywords : Anterior Cruciate Ligament Injury, autograft, bone patellar tendon bone, hamstring tendon